Tinjauan Format Ideal, Fungsi dan Estetika Buletin Binus University - Sari Wulandari (Bina Nusantara University, 2011)
Buletin BINUS is a communication medium that connects Binusian, contains information about events held at BINUS. Figures of this bulletin is BINUS University, either through the appearance and content of the newsletter itself, where the messages contained in explicit and implicit so that eventually will form a picture or image in the mind of the reader. This study examines the function and aesthetics in a format specific BULETIN which was published in 2008 and 2009. Reviewes carried out refers to the disciplines of Visual Communication Design. The purpose and benefits of this research is to use scientific and practical layout Buletin BINUS University and research results in the form of suggestions are ideal application of design elements for publication Buletin BINUS University, which is based on ease of implementation, the function of information, the effectiveness of media communications, and aesthetics. It is expected that the information in it will be delivered properly, can bring out the character right BINUS University and establish a positive image in the mind of the reader.